Os desafios em ser professora e professor monitores na pedagogia da alternância - Littig, Patrícia Hand (2021)
This research aims to know and understand the main challenges of being a teacher and a monitor in the Pedagogy of Alternation, in the scope of the professional career, working conditions and teacher training, besides discussing possibilities of facing them in order to enhance the work at São Bento do Chapéu Family Agricultural School in Domingos Martins. Furthermore, this work sought to historically contextualize Popular Education, Rural Education, Pedagogy of Alternation and its intertwinings: knowing-recognizing the historical constitution of São Bento do Chapéu Agricultural Family School and its contributions to the education of rural peoples in the region. The research is characterized by a qualitative approach. The study is outlined as a participant research, since the researcher was directly involved as a history teacher at the institution, a mother of a student, a former student and also as a granddaughter of one of the founders, as well. Among the challenges underscored by this work, in the professional career the turnover generated by the temporary assignment stands out; in the working conditions, the journey to EFA (Family Agricultural School) was signaled as an issue, a tiring routine as a consequence of the responsibility of the weekly shift and the adjustments imposed by the national base, as a challenge in the context of teacher training was the failure to contemplate the experiences in Rural Education in the curricula Degrees and the difficulty of participating in continuing education in the Pedagogy of Alternation (PA). Supported by the listed challenges, due to the nature of the professional Master's degree, as an educational product, we bring a proposal for continuing education built in a collective and participatory way with the school community, underping the discussion of possibilities for facing them.